Association of Vitamin D Levels with Chronic Liver Disease: A Case-Control Study - Neha P, Neha P; S V, Srinivasa; Praveen P, Praveen P (Journal of Neonatal Surgery, 2025)
Background: Vitamin D plays a critical role in bone metabolism, immune regulation, and cellular function. In patients with chronic liver disease (CLD), hepatic dysfunction impairs vitamin D metabolism, leading to deficiency. Emerging evidence suggests an association between low serum vitamin D levels and worsening liver disease severity. However, there remains a paucity of data exploring this relationship across diverse etiologies of CLD and validated severity indices. Therefore, this study aimed to assess the prevalence of vitamin D deficiency in CLD patients, examine its correlation with different etiologies of liver disease, and evaluate its association with disease severity using Child-Turcotte-Pugh (CTP) and Model for End-Stage Liver Disease (MELD) scores. Methods: A case-control study was conducted at RL Jalappa Hospital, Kolar, over one month. A total of 48 participants were enrolled 24 CLD patients (cases) and 24 healthy individuals (controls), matched for age and sex. Serum 25-hydroxyvitamin D [25(OH)D] levels were measured using ELISA. CLD severity was assessed using CTP and MELD scores. Patients were classified based on vitamin D status into deficient (<20 ng/mL), insufficient (20–29.9 ng/mL), sufficient (30–100 ng/mL), or toxic (>100 ng/mL). Statistical analysis included t-tests, ANOVA, chi-square, and linear regression using SPSS v22, with p < 0.05 considered significant. Results: Vitamin D deficiency was observed in 37.5% of CLD cases versus 16.7% of controls. In CLD patients, vitamin D levels declined with increasing bilirubin and decreasing albumin levels. Patients with bilirubin >3 mg/dL had mean vitamin D levels of 19.76 ± 7.11 ng/mL compared to 25.54 ± 6.78 ng/mL in those with bilirubin <2 mg/dL. Similarly, patients with albumin <3.0 g/dL had lower vitamin D levels (16.68 ± 6.49 ng/mL). Vitamin D levels were inversely associated with MELD and CTP scores. Regression analysis showed significant negative correlations: r = –0.6554 (MELD) and r = –0.7221 (CTP), p < 0.0001. Conclusion: Vitamin D deficiency is significantly more prevalent in CLD patients than in healthy controls and correlates strongly with disease severity. Routine assessment of serum vitamin D levels in CLD patients may aid in early identification of those at risk of progression and may serve as a valuable prognostic biomarker.